2014
DOI: 10.1016/j.optcom.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Law of refraction for generalised confocal lenslet arrays

Abstract: We derive the law of generalised refraction for generalised confocal lenslet arrays, which are arrays of misaligned telescopes. We have implemented this law of refraction in TIM, a custom open-source ray tracer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…We have shown that the light-ray-direction change upon transmission through gCLAs 7 is sufficiently general that structures of gCLAs can form pixellated transformation-optics devices in which the transformation between electromagnetic and physical space is piecewise affine. This is a surprisingly general and powerful result, and it has the potential to open up important new applications for transformation-optics ideas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the light-ray-direction change upon transmission through gCLAs 7 is sufficiently general that structures of gCLAs can form pixellated transformation-optics devices in which the transformation between electromagnetic and physical space is piecewise affine. This is a surprisingly general and powerful result, and it has the potential to open up important new applications for transformation-optics ideas.…”
Section: Discussionmentioning
confidence: 99%
“…The generalised law of refraction for gCLAs has been derived in Ref. 7 CLAs and gCLAs have interesting imaging properties. Ignoring the (small) sideways offset light rays experience upon transmission through the telescopes, planar, homogeneous, CLAs 10 and a subset of planar, homogeneous, gCLAs 8 have the property of stigmatically (ray-optically perfectly) imaging between all of object a b Figure 2.…”
Section: Generalised Refraction With Generalised Confocal Lenslet Arraysmentioning
confidence: 99%
“…Together, Eqns (24), (25) and (26) determine the direction e of the refracted light ray. We solve these equations as follows.…”
Section: Metrics Fermat's Principle and Refraction At Metric Inter-mentioning
confidence: 99%
“…11 We have used this idea to design and investigate windows that change the pieces of the beam by passing them through tiny Dove prisms, 12,13 which leads to mirroring of the ray direction, and we have used lenticular arrays (as used in 3D postcards) to build windows with this same functionality. 14 We have also designed and investigated [15][16][17] and built 18 arrays of micro-telescopes, which we _'---_ -1.r: Figure 1. Example of relativistic distortion.…”
Section: Introductionmentioning
confidence: 99%